Practices of traditional beef farmers in their production and marketing of cattle in Zambia - Mumba, C.; Häsler, Barbara; Muma, J.B.; Munyeme, M.; Sitali, D.C.; Skjerve, E.; Rich, Karl M. (Springer, 2018)
Understanding the practices of traditional cattle farmers in developing countries is an important factor in the development of appropriate, pro-poor disease control policies, and in formulating regional-specific production incentives that can improve productivity. This paper describes the production, husbandry practices, economics, and constraints of traditional cattle farming in Zambia. A cross-sectional study design was used to obtain data from traditional cattle farmers (n = 699) using a structured questionnaire. Data analyses were carried out using SPSS and STATA statistical packages. The results revealed that the majority [65% (95% CI: 59.3–71.1)] of farmers practised a transhumant cattle herding system under communal grazing. In these transhumant herding systems, animal husbandry and management systems were found to be of poor quality, in terms of supplementary feeding, vaccination coverage, deworming, uptake of veterinary services, usage of artificial insemination, and dip tanks all being low or absent. East Coast Fever was the most common disease, affecting 60% (95% CI: 56.4–63.7) of farmers. Cattle sales were low, as farmers only sold a median of two cattle per household per year. Crop farming was found to be the main source of farm income (47%) in agro-pastoralist communities, followed by cattle farming (28%) and other sources (25%). The median cost of production in the surveyed provinces was reported at US$316, while that of revenue from cattle and cattle products sales was estimated at US$885 per herd per year. This translates to an estimated gross margin of US$569, representing 64.3% of revenue. There is considerable diversity in disease distribution, animal husbandry practices, economics, and challenges in traditional cattle production in different locations of Zambia. Therefore, to improve the productivity of the traditional cattle sub-sector, policy makers and stakeholders in the beef value chain must develop fit-for-purpose policies and interventions that consider these variations.